Programmable stimulator E.P.2.1. - Mondaca, E.; Valenzuela, Z.; Rodríguez, G.; Nieves, J. (Revista Mexicana de Ingenieria Biomedica, 2018)
The E.P.2.1. is a device that generates complex stimulation pulses, designed in a microcomputer, created in the INC, and also composed on a digital/analog conversion node and an interface for communication with a PC. The stimulation is controlled with a program made in FORTH, which also relates to E.P.2.1. with the PC; in this, the program manager makes it possible to visualize one of the five modes of stimulation, save it on disk and transmit it to the stimulator at any time.